THE “HUASO RAIMuNDO’S GANGS”. SOCIAL NETWORKS AND DELICTIVE TRANSITIONALITY IN SANTIAGO AND ITS SURROuNDINGS (1882-1911) - Ayala Cordero, Ignacio (Revista de Historia Social y de las Mentalidades, 2024)
As known thief, Nonato Orellana Aviles appears as a transitional subject in the context of capitalist modernization in Chile. Represents the process of claim depeasantization and disciplining of rural peonage, in addition to the forms of incorporation into the city from the transgression. Transitionality expression is also the diversity of media documentaries crimes that had as protagonist in a space of time ranging from 1904 to 1911. The objective of this article is to analyze, incorporating micro-historical approach and social network analysis, the practice developed by criminal “Huaso Raimundo’s gangs” from strategic and organizational dimensions. While day survival strategy, not subordinated to the work ethic, be an alternative to proletarianization; while through its organizational features, such strategy would be designed socially incorporated in the process of setting up the “criminal underworld” of Santiago and its surroundings.